Življenje in delo fitocenologa dr. Milana Piskernika (1925-2006) - Wraber, Tone (Gozdarski vestnik, 2007)
In the first part of the article, the author describes in detail the life and scientific, research and professional work of Dr. Milan Piskernik, and in the second part is collected a chronology of all his publications and available manuscripts.
Keywords: Piskernik, Milan; 1925-2006; biografije